Biodiversity in the Amazon: Origin Hypotheses, Intrinsic Capacity of Species Colonization, and Comparative Phylogeography of River Otters (Lontra longicaudis and Pteronura brasiliensis, Mustelidae, Carnivora) and Pink River Dolphin (Inia sp., Iniidae, Cetacea) (2018)
We sequenced mitochondrial genes of otter (Lontra longicaudis and Pteronura brasiliensis) and dolphin (Inia sp.) species to provide new systematics data and to test hypotheses that offer explanations as to the Amazon’s biodiversity. Four of the 11 hypotheses tested --Paleogeography (PH), Recent Lagoon (RLH), Hydrogeological Recent Change (HRCH), and Refugia (RH)-- support the evolution of these three species. As part of this comparative phylogenetic study, we also considered the degree of water dependence of each species. For the least water dependent of the three species, L. longicaudis, only HRCH and RH had an influence on genetic structure, although it was relatively minor. For the more water dependent otter species, P. brasiliensis, our analyses stressed the significance of a single PH event along with two lesser important PH events. However, its gene diversification basically occurred during the Pleistocene and our analyses did detect a relatively small influence of HRCH and RH. For the completely water dependent species, Inia, we detected two significant PH events. Its genetic structure was considerably more developed than in either otter species, although the Pleistocene was a very important period of genetic diversification for the pink river dolphins (HRCH and RLH). Each species has ancestors with different geographical origins and genomes with different capacities to colonize—making it difficult to rely on a generalized hypothesis to understand the origins of the Amazon’s extremely rich biodiversity. © 2017, Springer Science+Business Media New York.